Modelling and onsite testing on dynamic thermal responses of built environment in passive solar rooms on Tibetan plateau - Zhang, Yin; Han, Wenyang; Qi, Yicong (Frontiers in Energy Research, 2024)
It of great importance in assessing built thermal environment level and evaluating corresponding indoor air conditioning demand for energy conservation in construction sectors. Nevertheless, because of the unique meteorological features in plateau area, classical building performance simulation approach contributes to thermal performance evaluation errors since most design codes or standards relies on low attitude regions. In this paper, a modified and improved dynamic thermal design model is put forward for built environment and energy consumption estimation for passive buildings for plateau buildings. Moreover, the simplified experiment is set up to monitor dynamic thermal responses for modelling building. The testing validation illustrate that the onsite measurement accuracy level is quite acceptable for engineering applications with less than 30% relative change range coefficient. Besides, the experiment data demonstrates that window-to-wall ratios, architectural orientation, thermal insulation coefficients, have substantial impacts for solar heat gains in plateau buildings. The study renders building design guidance for energy conservation in high altitude plateau areas.